2021
DOI: 10.5430/rwe.v12n2p132
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital and Manufacturing Output in Nigeria: A Micro-Data Survey

Abstract: In attempting to explain the rather inconsistent growth of manufacturing industries in Nigeria, this study seeks to investigate the effect of human capital on manufacturing output in the Nigerian industrial firms. The study adopts human capital theory as a basis for the theoretical framework. Micro-data from the World Bank Enterprise Survey (2014) is utilised to perform Spearman Correlation in investigating the specific effects of HC on manufacturing value-added for Nigerian industries. High-school education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Coupled with that, the leapfrogging hypothesis states that ICT is the platform upon which developing economies can skip developmental stages (Steinmueller, 2001;Sein & Harindranath, 2004;Avgerou, 2017;Adeleye et al, 2022a;Adeleye et al, 2022b). Labour is an critical element for growth (Shahid, 2014;Olarewaju et al, 2021;X. Zhang & Wang, 2021), Internet usage contributes to economic productivity (Visser, 2019;Shahnazi, 2021), education which is human capital exerts a positive impact on growth (Čadil et al, 2014;Pelinescu, 2015), quality institutions provide the enabling environment for growth to thrive (Acemoglu & Robinson, 2010;Bahamonde & Trasberg, 2021), and lastly capital is a vital growth input (Lach, 2010;Ahmed et al, 2016;Adeleye et al, 2021b).…”
Section: Variables Justification and Expectationsmentioning
confidence: 99%
“…Coupled with that, the leapfrogging hypothesis states that ICT is the platform upon which developing economies can skip developmental stages (Steinmueller, 2001;Sein & Harindranath, 2004;Avgerou, 2017;Adeleye et al, 2022a;Adeleye et al, 2022b). Labour is an critical element for growth (Shahid, 2014;Olarewaju et al, 2021;X. Zhang & Wang, 2021), Internet usage contributes to economic productivity (Visser, 2019;Shahnazi, 2021), education which is human capital exerts a positive impact on growth (Čadil et al, 2014;Pelinescu, 2015), quality institutions provide the enabling environment for growth to thrive (Acemoglu & Robinson, 2010;Bahamonde & Trasberg, 2021), and lastly capital is a vital growth input (Lach, 2010;Ahmed et al, 2016;Adeleye et al, 2021b).…”
Section: Variables Justification and Expectationsmentioning
confidence: 99%
“…It is all about creating perfect training circumstances. Neo-human capital theory proposed in the 1980s that businesses should train their personnel in a systematic manner to improve the workforce's flexibility and suppleness, as well as their openness to modernization [25,26].…”
Section: Human Capital Theorymentioning
confidence: 99%
“…They found that the increase in the level of innovative human capital inhibits, to some extent, the positive effect of external knowledge sourcing on high-quality innovation in manufacturing. In addition, scholars have found that human capital can promote the development of the manufacturing industry through technological innovation [16][17][18][19], improving production efficiency [20,21], improving consumption structure [22], and promoting the accumulation of productive service industries [23]. Under the impetus of the new industrial revolution, innovative human capital, scientific and technological talents, and other high-level human capital have gradually become hot spots for scholars' attention.…”
Section: Introductionmentioning
confidence: 99%